DANA PUNIA WUJUD INTEGRASI SOSIAL UMAT HINDU - Komang Heriyanti (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Social integration is something that society aspires to, especially a pluralistic society. However, it is also possible that social integration is important for communities who share the same beliefs and culture. In social life there has been a lot of friction or conflict between people who have the same belief or different beliefs, this is one of the implications of the existence of different points of view from each individual. The role of religion in this case still needs to be strengthened to foster harmony in society. Hinduism has taught many values of togetherness with the aim that society is well integrated. One of the teachings that can be implemented in relation to developing social integration is dana punia. Dana punia fund activity is a person's concern for others. Apart from that, dana punia activities can also be carried out by donating to repair holy places as a form of devotion to Ida Sang Hyang Widhi Wasa. Keywords: Hinduism, Punia, Social